The Phenomenon of News and Stories In A Collection of Poetry Ada Apa Hari Ini, Den Sastro? By Sapardi Djoko Damono - I Gusti Ayu Agung Mas Triadnyani; I Ketut Nama (Proceedings of AICS - Social Sciences, 2021)
This paper discusses the issue of binary opposition, especially dealing with the opposite genres between fiction and non-fiction in literary works. Commonly fiction is assumed to concern only with imaginations, while non-fiction with realities or facts. This issue is applied to examine the poems of number 1-9 through the work, titled